'Bhora Mugedhi versus Bhora musango': The interface between football discourse and Zimbabwean politics. (March 2016) - Ncube, Lyton
Football is the most popular sport in Zimbabwe and across the globe. It has been asserted elsewhere that the game is not limited to scoring goals on the pitch but that this also occurs in politics and power struggles. This study explores the interface between football discourse and politics during elections in Zimbabwe in July 2013. The study is based on the premise of a neo-Gramscian perspective which views popular culture (including football) as a terrain of ideological struggle. It utilises an ethnographic approach to make a 'thick description' of the relationship between football discourse and contemporary Zimbabwean politics. The study employs critical discourse analysis on purposively selected political campaign speeches, political advertisements, songs by politicians, and comments posted and circulated in social media such as Facebook and Whatsapp during and after the election period by 'ordinary' Zimbabweans. The findings suggest that political parties, specifically the Zimbabwe African National Union Patriotic Front (ZANU PF) and the Movement for Democratic Change (MDC-T) appropriated football images, symbols, metaphors and discourses in their campaign communications. Zimbabwe symbolically became a football pitch where these two main rivals battled to score political points. 'Ordinary' Zimbabweans resembled the fans and/referees in the game whose vote symbolically became the act of scoring goals for ZANU PF; while for MDC-T it was akin to giving a red card to the ZANU PF party.